Ultraporous Amine-Functionalized Organosilicas: Tuning Morphology and Surface Chemistry for Adsorption Applications - Marlena Bytniewska; Kacper Latusek; Maria Powęzka; Marcin Kuśmierz; Oliwia Kapusta; Mariusz Barczak (Molecules, 2025)
Highly porous organosilicas were synthesized via direct co-condensation of two monomers, bis (triethoxysilyl) benzene and aminopropyltriethoxysilane, by adjusting the time between consecutive additions of the monomers and the ageing time of the as-obtained samples. The resulting organosilicas exhibited high porosities, with total pore volumes exceeding 2.2 cm3/g. Alongside detailed insights into the morphology, structure, and surface chemistry via a broad spectrum of various instrumental techniques, the obtained ultraporous amine-functionalized organosilicas were tested as adsorbents of diclofenac sodium, chosen here as a model drug. The results revealed remarkable differences in the physicochemical properties and adsorption efficiencies among the obtained samples, confirming that the time gap between the addition of the monomers and ageing time can be used to tune the morphological, structural, and chemical features of the obtained organosilicas and, as a consequence, their sorption efficiencies.